2018
DOI: 10.3832/ifor2291-010
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive variation in physiological traits of beech provenances in Central Europe

Abstract: (1) Current climate changes can led to a decline of local beech populations fully adapted to previous climate conditions. In this context, the issue of variation in adaptive traits becomes important. A field experiment with 18-year-old trees of Fagus sylvatica L. was conducted on provenance plot located in Tále (Central Slovakia), where physiological responses of five beech provenances originating from contrasting sites along an altitudinal gradient from 55 to 1100 m a.s.l. across the range of the natural beec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
2
7
0
Order By: Relevance
“…The fir provenances originating from relatively high altitudes (from wetter and colder localities) achieved and maintained relatively high efficiency of PSII photochemistry, even more they enhanced their efficiency at PSII level after mild water stress. These findings concur with those from provenances of other species, i.e., Fagus sylvatica (Kučerová et al 2018, Quercus suber L. (Aranda et al 2005), Picea abies (Oleksyn et al 1998, Jamnická et al 2019, and also Abies alba (Peguero-Pina et al 2007, reflecting the variation in the adaptation and acclimation abilities of forest tree species under conditions of a changing climate with possible use for forestry purposes.…”
Section: Discussionsupporting
confidence: 82%
“…The fir provenances originating from relatively high altitudes (from wetter and colder localities) achieved and maintained relatively high efficiency of PSII photochemistry, even more they enhanced their efficiency at PSII level after mild water stress. These findings concur with those from provenances of other species, i.e., Fagus sylvatica (Kučerová et al 2018, Quercus suber L. (Aranda et al 2005), Picea abies (Oleksyn et al 1998, Jamnická et al 2019, and also Abies alba (Peguero-Pina et al 2007, reflecting the variation in the adaptation and acclimation abilities of forest tree species under conditions of a changing climate with possible use for forestry purposes.…”
Section: Discussionsupporting
confidence: 82%
“…In the present study, the differences among provenances, were found to be statistically significant for all ten measured stomatal parameters (Table 2). This result suggests a high genetic diversity of European beech, which has been already evidenced with respect to certain anatomical (STOJNIĆ et al, 2016a;HAJEK et al, 2016), morphological (IVANKOVIĆ et al, 2011MEKIĆ et al, 2010), phenological (CHMURA and ROZKOWSKI, 2002;BALLIAN et al, 2015) and physiological (STOJNIĆ et al, 2010;KUČEROVÁ et al, 2018) traits. The difference between provenances, applies to different functional traits, are assumed to be the result of the various genetic architecture of provenances, which has evolved as a result of local adaptation, in response to diverse selective pressure in areas of beech distribution (JUMP et al, 2006;STILL et al, 2005;STOJNIĆ et al, 2016b).…”
Section: Resultssupporting
confidence: 58%
“…The present study focus on evaluation of intra-and inter-provenance variation of leaf stomatal traits of examined European beech provenances using methods of univariate (ANOVA, Tukey's HSD test), and multivariate (PCA, discriminant analysis and cluster) statistical analyses. Although a certain study (KUČEROVÁ et al, 2018) of the variability of European beech provenances included the measurement of stomatal traits, to the best of our knowledge, this study is the first to demonstrate an analysis of variation based on the above-mentioned statistical methods. Furthermore, the present study has shown the importance of an assessment of examined stomatal traits in the discrimination of provenances.…”
Section: Introductionmentioning
confidence: 99%
“…The origin of different beech provenances can also affect seedling performance because of interactions with the microbiome of soil communities (Manzanedo et al 2018), feeding back to effect drought tolerance. Besides location, the elevation of origin affects a suite of leaf-level traits related to stress tolerance and photosynthesis, as found in a comparison of five beech provenances along an elevational gradient in Czechia (Kučerová et al 2018). Intraspecific differences in strategy involving trade-offs between growth and defense or stress tolerance are also visible in the metabolite profiles of leaves across beech provenances (Aranda et al 2017).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 87%